Production of rocket with organic fertilization and doses of bovine urine - Cruz, Adiel Felipe da Silva (2021)
Organic fertilization in vegetable production improves soil quality and nutrient availability for plants. In this context, the objective of this study was to evaluate the effect of doses of bovine urine combined with organic fertilizers based on cattle manure and compost, on the cultivation of rocket cv. "Agatha". The experiment was carried out at the Federal University of the Agreste of Pernambuco (UFAPE), under field conditions. The treatments consisted of six doses of bovine urine (20, 40, 60, 80, 100, 120 mL) and applications of organic fertilizer based on tanned bovine manure and compost. The experimental design was randomized blocks in a 6 x 2 factorial scheme, with four replications totaling 48 experimental plots. Plant height, number of leaves, fresh and dry mass of shoots and root-to-shoot ratio were evaluated. Organic fertilization was beneficial for all studied variables. It was verified that the increase in the doses of bovine urine using compost provided an increase in the production of dry mass of the aerial part and in the number of leaves. On the other hand, the isolated effect of bovine urine was demonstrated a reduction in the shoot root ratio and an increase in fresh mass and plant height.